2020
DOI: 10.1093/brain/awaa016
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of lacosamide on Nav1.7 variants from responsive and non-responsive patients with small fibre neuropathy

Abstract: Small fibre neuropathy is a common pain disorder, which in many cases fails to respond to treatment with existing medications. Gain-of-function mutations of voltage-gated sodium channel Nav1.7 underlie dorsal root ganglion neuronal hyperexcitability and pain in a subset of patients with small fibre neuropathy. Recent clinical studies have demonstrated that lacosamide, which blocks sodium channels in a use-dependent manner, attenuates pain in some patients with Nav1.7 mutations; however, only a subgroup of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…3. Recently a clinical trial has found lacosamide to be efficacious in reducing pain and well-being of SFN patients with SCN9A mutations [27]; however, the effect was linked to subset of SCN9A mutations [74].…”
Section: Heritable Small Fibre Neuropathymentioning
confidence: 99%
“…3. Recently a clinical trial has found lacosamide to be efficacious in reducing pain and well-being of SFN patients with SCN9A mutations [27]; however, the effect was linked to subset of SCN9A mutations [74].…”
Section: Heritable Small Fibre Neuropathymentioning
confidence: 99%
“…The anticonvulsant lacosamide, acting on Nav1.3, Nav1.7, and Nav1.8 channels, was tested in patients with Nav1.7-mutation-related small-fibre neuropathy, with promising findings in a subgroup of patients [ 33 ]. Labau and colleagues, using voltage-clamp recordings, found a preferential effect of lacosamide on Nav1.7 variants in patients who were responsive to lacosamide via a hyperpolarizing shift in the voltage dependence of both fast and slow inactivation and enhancement of use-dependent inhibition [ 53 ]. In addition, recent studies have shown that carbamazepine, at clinically achievable concentrations, acts via a new mode of action as an activation modulator of select mutant Nav1.7 channels [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in recombinant systems suggest carbamazepine affects these mutant channels by modulating inactivation as opposed to restoring normal channel activation. Likewise, a recent study identified a striking correlation between lacosamide modulation of Nav1.7 mutation channels in patients and clinical efficacy (Labau et al, 2020). These observations suggest that the underlying molecular driver of pathologic neural activity may constrain the efficacy of Nav blockers based on their particular mechanism of action.…”
Section: Characterization Of Vixotriginementioning
confidence: 93%